2014
DOI: 10.1002/jso.23627
|View full text |Cite
|
Sign up to set email alerts
|

The effect of health insurance status on the treatment and outcomes of patients with colorectal cancer

Abstract: Although uninsured and Medicaid patients receive recommended adjuvant therapy comparable to other patients, they present with later stage disease and have a worse OS. Future studies are needed to better explain these disparities especially in the light of changing healthcare climate in the US.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

7
51
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 78 publications
(60 citation statements)
references
References 18 publications
7
51
1
Order By: Relevance
“…2, 22, 23 Additionally, insurance status seems to greatly impact survival outcomes. While this is not the focus of this study, similar findings have been shown in other cancer types 24, 25 and warrant further investigation as an important disparity in health care delivery and outcomes.…”
Section: Discussionsupporting
confidence: 69%
“…2, 22, 23 Additionally, insurance status seems to greatly impact survival outcomes. While this is not the focus of this study, similar findings have been shown in other cancer types 24, 25 and warrant further investigation as an important disparity in health care delivery and outcomes.…”
Section: Discussionsupporting
confidence: 69%
“…Many factors including tumor histology, control of extracranial disease, and PS impact a patient’s overall survival (8). It has been reported that uninsured and underinsured cancer patients often have delayed diagnosis and inferior outcomes (911). Our institutional series is unique in that a larger percentage of our patient population is African-American, on Medicaid or on Medicare compared to previous publications reporting health disparities in patients treated for brain metastases (10, 11).…”
Section: Introductionmentioning
confidence: 99%
“…In 2014, Walker et al used the Surveillance, Epidemiology and End Results (SEER) database to evaluate nearly half a million patients diagnosed with one of the ten most common causes of cancer mortality [ [9]. While increased rates of distant or advanced-staged disease among uninsured and Medicaid-insured patients may contribute to lower rates of cancer-directed treatment, socioeconomic factors including an inability to cover out-of-pocket treatment expenses and limited access to care must also be considered.…”
mentioning
confidence: 99%